MENTAL HEALTH OF PATIENTS UNDER ONCOLOGICAL TREATMENT DURING THE COVID-19 PANDEMIC (CIPEEX, 2022)
THE CORONAVIRUS DISEASE 2019 (COVID-19) HAS HAD REPERCUSSIONS IN SEVERAL DIMENSIONS, AFFECTING ASPECTS SUCH AS SOCIOECONOMIC, EDUCATIONAL, AND HEALTH ASPECTS, CORROBORATING THE INCREASE IN MENTAL DISORDERS IN THE GENERAL POPULATION. CONSEQUENTLY, PATIENTS UNDERGOING CANCER TREATMENT ARE PSYCHOLOGICALLY AFFECTED BY THIS SCENARIO, WHICH CAN REFLECT DIRECTLY ON THERAPEUTIC ADHERENCE, PROGNOSIS, AND QUALITY OF LIFE. THUS, THE PRESENT STUDY AIMED TO ANALYZE THE IMPACTS OF THE COVID-19 PANDEMIC ON THE MENTAL HEALTH OF ONCOLOGY PATIENTS AT THE ANÁPOLIS CANCER UNIT - UNICCA. THIS IS A DESCRIPTIVE, CROSS-SECTIONAL STUDY, OF QUANTITATIVE APPROACH, INVOLVING PATIENTS BETWEEN 18 AND 90 YEARS OF AGE IN ANTINEOPLASTIC TREATMENT FROM MARCH 2020 TO MARCH 2021, BEING USED FOR DATA COLLECTION THE GENERAL HEALTH QUESTIONNAIRE (QSG-12). PARTICIPATED IN THE RESEARCH 133 PATIENTS, 66.2% WERE FEMALE; AGE RANGED FROM 20 TO 87 YEARS, WITH PREVALENCE BETWEEN 50 AND 70 YEARS (54.1%); THE PREDOMINANT MARITAL STATUS WAS "MARRIED" (52.6%); BELONGING TO THE CATHOLIC RELIGION (61.7%); MOST WITH LOW EDUCATION (55.7%); AND WITH AN INCOME OF UP TO ONE MINIMUM WAGE (58.6%). REGARDING MENTAL HEALTH, IT WAS NOTICED THAT THE FEELING OF AGONY (42.1%), THE INABILITY TO CONCENTRATE ON WHAT THEY DO (45.1%), AND THE LOSS OF SLEEP BECAUSE OF WORRIES (45.1%) WERE THE NEGATIVE ASPECTS MOST REPORTED. IT WAS ALSO NOTED THAT THERE WAS NO SIGNIFICANT DECREASE IN OUTPATIENT VISITS DUE TO THE PANDEMIC, AND THE ASPECTS MOST CONSIDERED BY THOSE WHO REDUCED THEIR VISITS WERE SOCIAL ISOLATION AND THE FEAR OF CONTRACTING THE COVID-19 DISEASE. THEREFORE, DIRECT ENCOURAGEMENT TO THIS PUBLIC IS NECESSARY, HELPING PATIENTS TO COPE WITH THE DISEASE. FINALLY, THERE SHOULD BE A GREATER ENCOURAGEMENT OF RESEARCH ON THIS SUBJECT IN ORDER TO PROVIDE BETTER CARE TO THIS PROFILE OF PATIENTS.
Keywords: covid-19; oncology; pandemic; mental health; treatment